Transforming the professoriate in Africa: Contributions/considerations from future professors fellows of the future professors programme - Waghid, Z.; Madzivhandila, T.; Govender, S.; Sabiu, S. (South African Journal of Higher Education, 2024)
This Special Issue focuses on the perspectives of Future Professors Programme (FPP) fellows’ creative practices designed to fulfil the need to transform the existing university curricula which have been implemented in various disciplines by the professoriate It looks at articles whose foci include: the role interdisciplinarity can play concerning the need to cultivate social justice and social transformation, what these academics understand of the significance of digital transformation as well as Information and Communication Technology (ICT) in their practices whose purpose is the production of critically engaged and highly competitive students as citizens of society, and how their existing university practices can be more aligned with Indigenous Knowledge Systems (IKS).